EVALUATION OF FORAGE YIELD AND SILAGE QUALITY OF SWEET SORGHUM IN THE EASTERN MEDITERRANEAN REGION - C. Yucel1; M. E. Erkan (Journal of Animal and Plant Sciences, 2020)
Different sweet sorghum varieties were ensiled and silage quality attributes were determined in the present study. M81-E, Ramada, Roma, Topper-76, UNL Hybrid and No91 sweet sorghum (Sorghum bicolor var. saccharatum (L.) Mohlenbr.) genotypes were used as the plant material for the study. Field experiments were conducted at the experimental fields of Eastern Mediterranean Agricultural Research Institute (Dogankent-Adana) in the years 2016 and 2017 under second-crop conditions (June-October) in a randomized complete block design with four replications. Average green herbage yield, dry matter yield, crude protein yield, crude protein (CP) ratio, neutral detergent fiber (NDF), acid detergent fiber (ADF), dry matter intake (DMI) and relative feed value (RFV) varied between 151.5-188.7 Mg ha−1; 46.6-61.2 Mg ha−1; 2166-2905 kg ha−1; 4.08-5.22%, 39.11-43.10%, 24.31-28.36%, 2.81-3.11%, and 148.3-168.4. Present findings revealed that M81-E, Topper-76, UNL hybrid and No91 varieties were higher with herbage and DM yield while Ramada and Roma were higher with silage quality attributes. It was observed that the sweet sorghum varieties at second-crop growing period (June-October) under Eastern Mediterranean (Adana) conditions for 100-120 days had green herbage, dry matter and crude protein yields more than 180 Mg ha−1, 50 Mg ha−1 and 2300 kg ha−1, respectively. These varieties had RFV of above 150. Such a value was greater than the RFV of several other forage crops.
Keywords: Sweet sorghum; silage; cultivar; quality